2015
DOI: 10.1111/vco.12137
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐based cytology and cell block immunocytochemistry in veterinary medicine: comparison with standard cytology for the evaluation of canine lymphoid samples

Abstract: Liquid-based Cytology (LBC) consists of immediate wet cell fixation with automated slide preparation. We applied LBC, cell block (CB) and immunocytochemistry to diagnose canine lymphoma and compare results with conventional cytology. Samples from enlarged lymph nodes of 18 dogs were collected and fixed in preservative solution for automated slide preparation (LBC), CB inclusion and immunophenotyping. Two CB techniques were tested: fixed sediment method (FSM) and agar method (AM). Anti-CD79a, anti-Pax5, anti-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 29 publications
2
38
0
1
Order By: Relevance
“…Ki67 ICC has also proved to be an excellent method of differentiation between non-neoplastic and neoplastic proliferation of lymphatic tissue (Bauer et al 2007, Fernandes et al 2015. Moreover, Fournel--Fleury et al (1997b) have confirmed that immunocytochemistry using Ki67 antibodies is a useful method of determination of proliferative activity of lymphoma cells, and have revealed high concordance between the results of Ki67 immunocytochemistry and immunohistochemistry performed on histological samples of lymphoma tissues.…”
Section: Application Of Cytology In Canine Lymphomasmentioning
confidence: 48%
See 3 more Smart Citations
“…Ki67 ICC has also proved to be an excellent method of differentiation between non-neoplastic and neoplastic proliferation of lymphatic tissue (Bauer et al 2007, Fernandes et al 2015. Moreover, Fournel--Fleury et al (1997b) have confirmed that immunocytochemistry using Ki67 antibodies is a useful method of determination of proliferative activity of lymphoma cells, and have revealed high concordance between the results of Ki67 immunocytochemistry and immunohistochemistry performed on histological samples of lymphoma tissues.…”
Section: Application Of Cytology In Canine Lymphomasmentioning
confidence: 48%
“…In canine oncology it is especially valuable for diagnosing the most common subtypes of lymphomas (Fournel-Fleury et al 1997a, Fournel-Fleury et al 2002, Comazzi et al 2014. Recently, many authors have recommended using cytology as a sufficient diagnostic method for canine lymphomas, especially if supported by immunocytochemistry and/or flow cytometry (Messic 2008, Regan et al 2012, Martini et al 2013, Comazzi et al 2014, Curran and Thamm 2015, Fernandes et al 2015, Jankowska et al 2015. The great advantage of this method is the possibility of performing immunocytochemical staining.…”
Section: Application Of Cytology In Canine Lymphomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Pax5 staining was used for B-cell identification in a complicated case report on multicentric B-cell lymphoma with neurolymphocytosis (Schaffer et al 2012). Pax5 was also employed in a study of inflammatory processes: spirocercosis-induced nodular formation in dogs (Dvir et al 2011), and was also used in an immunocytochemistry by liquid-based cytology and tissue transfer technique for immunophenotyping in canine non-Hodgkin lymphoma (Stone and Gan 2014;Fernandes et al 2015). The sensitivity and specificity of Pax5 immunohistochemistry for B-cell lymphomas when compared to heteroduplex polymerase chain reaction for antigen receptor rearrangements of IgH primer sets for B-cells, were 48% and 100%, respectively (Sirivisoot et al 2016).…”
Section: Discussionmentioning
confidence: 99%